The relativity of socio-cultural factors on young people’s access to higher education in Africa - Durowaiye, B.E.; Khan, S. (South African Journal of Higher Education, 2017)
The development of sociological discourse and research have focused attention on social issues from one that is primarily concerned with individual rationality to an explanation of cultural norms, values, religious beliefs and practices that places individuals within their social context. Through a critical review of existing literature which identifies the social processes through which young people’s access are mediated in African context, this paper developed a framework which provides understanding of how young people are confronted with various contradictory norms and social constrains with respect to their gender, economic status and relational positions in gaining access to higher education. Essentially, analysis of various empirical and non-empirical studies across Africa provided a clear conclusion that the capacity for securing access and retaining enrolment in higher educational institutions is not entirely determined by the rational considerations of young people, but principally depends on the various contexts in which certain beliefs, norms and values take place.